The Effect of Age on the Quality of Semen Turkeys (Meleagris gallopavo) - Riyan Nugroho Aji; Ismaya Ismaya; Sri Harimurti; Heru Sasongko; Sigit Bintara; Widya Asmarawati (Faculty of Animal Science, Universitas Gadjah Mada, 2018)
The purpose of this study was to observe the macroscopic and microscopic quality of Bronze turkey fresh semen on various ages. The observed toms were at the ages of 9 to 10 months (P1), 13 to 14 months (P2), and 17 to 18 months (P3), with each taken from 3 different toms. The collection was done by abdominal massage, and collected for 3 times a week in triplicate. This data was analyzed by analysis of variance (ANOVA) in a completely randomized design, followed by Duncan's New Multiple Range Test (DMRT) if there was any difference. The results showed that the average volume of turkey fresh semen were P1 (0.16 ± 0.04 ml), P2 (0.13 ± 0.02 ml), and P3 (0.10 ± 0.02 ml). The average pH of fresh semen were P1 (7.19 ± 0.05), P2 (7.12 ± 0.10), and P3 (7.06 ± 0.06). The average motility percentage of fresh semen were P1 (78.11 ± 1.38%), P2 (82.55 ± 1.17%), and P3 (74.55 ± 4.16%). The average viability percentage of fresh semen were P1 (78.63 ± 1.55%), P2 (83.26 ± 1.54%), and P3 (79.20 ± 1.06%). The average abnormal percentage of spermatozoa were P1 (3.01 ± 0.04%), P2 (3.04 ± 0.88%), and P3 (3.21 ± 0.44%). In conclusion, the best fresh semen quality is found on toms aged from 13 to14 months (P2). Furthermore, at the age 17 to18 months and more, the semen quality was decreased.